Evaluation of Drainage System on Jalan Slamet Riyadi and the Mahakam IV Bridge Approach Road, Samarinda City - Daru Purbaningtyas Kusumo; Dina Sandrina; S S N Banjarsanti (Civil Engineering Dept, Balikpapan State Polytechnics, 2023)
The construction of the Mahakam IV Bridge and the geometric changes to the Slamet Riyadi road in the vicinity have caused inundation problems on the main road section and the Mahakam IV Bridge Approach Road on the Samarinda City side. It is necessary to evaluate the drainage system in that location to prevent inundation that disturbs traffic and causes road damage. Flood discharge is analyzed based on rainfall data and using a Modified Rational Method. The design rain is calculated by a method that satisfies the goodness of fit test. The evaluation results show that the flood discharge to the channel is greater than the capacity channel. An alternative solution is to add a direct flow path to the Mahakam River in the form of long storage. And to speed up the drying on the bridge approach road, it is necessary to increase the number of street inlets and repair the culverts that drain water to the Mahakam River